Managing the Organization at the Stage of Growth: An Overview - Arman Hj Ahmad (Cita konsultindo, 2022)
It is always become a dream of every entrepreneur to witness the growth of their venture. Growing venture is a signal of success. However, there is not easy to manage the growth of every venture in the organizational lifecycle. The ability to manage the stage of growth by entrepreneurs will determine whether the venture able to reach other phases in the lifecycle of not. There are many considerations need to take into account if the entrepreneurs want to achieve the ultimate stage in the lifecycle and off course so many sacrifice need to be done for that. Careful analyses of fourteen articles with different themes on organizational growth yield some insights on issues prevalent in the matter. Finally, this paper proposes an integrated model for the suggestions on how business venture could manage those growths. The suggestions are constructed based on insights drawn from the analyses of the articles. The suggested strategies may be used as a guide for any business ventures and may be useful tools for consultants to use in handling tasks relating to the managing of the stage of growth in the organizational lifecycle